ПОКАЗАТЕЛИ НЕКОТОРЫХ ИММУНОЛОГИЧЕСКИХ ПОКАЗАТЕЛЕЙ У ЖЕНЩИН ДЕТОРОДНОГО ВОЗРАСТА, ПЕРЕНЕСШИХ COVID-19, В УСЛОВИЯХ ПРИАРАЛЬЯ - Каландарова, Амина Нуруллаевна; Жиемуратова, Гулпаршын Кошкинбаевна; Кадырова, Айгуль Мийирбековна (FORCIPE, 2022)